2020
DOI: 10.1017/pab.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous–Paleogene plant extinction and recovery in Patagonia

Abstract: The Cretaceous–Paleogene (K/Pg) extinction appears to have been geographically heterogeneous for some organismal groups. Southern Hemisphere K/Pg palynological records have shown lower extinction and faster recovery than in the Northern Hemisphere, but no comparable, well-constrained Southern Hemisphere macrofloras spanning this interval had been available. Here, macrofloral turnover patterns are addressed for the first time in the Southern Hemisphere, using more than 3500 dicot leaves from the latest Cretaceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 130 publications
(315 reference statements)
0
29
0
Order By: Relevance
“…This distinct pattern implies that contemporary asteroid impact winter models, which predict an impact winter lasting longer than a year, coupled with extreme desiccation (~85% reduction in precipitation according to Chiarenza et al, 2020) and a transient episode of permafrost conditions (Chiarenza et al, 2020;Tabor et al, 2020), probably are correct. Such an interpretation is bolstered by the perspective that high-latitude regions in the Southern Hemisphere, such as Patagonia, Argentina, were once regarded as refugia for plants during the K/Pg mass-extinction event (Barreda et al, 2012), although this changed when Stiles et al (2020) discovered evidence of a megafloral mass-extinction event of approximately the same magnitude (~90% of species) and nature (destruction of broadleaved evergreen forests, resulting in leaf physiognomicbased drops in mean annual temperatures of −5°C) as that described from western North America by Johnson (1996Johnson ( , 2002, Wilf et al (2003) and Wilf and Johnson (2004). Although these discoveries are new, they were nonetheless predicted by Iglesias et al (2011) following the description of an early Paleocene megafloral assemblage (Iglesias et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This distinct pattern implies that contemporary asteroid impact winter models, which predict an impact winter lasting longer than a year, coupled with extreme desiccation (~85% reduction in precipitation according to Chiarenza et al, 2020) and a transient episode of permafrost conditions (Chiarenza et al, 2020;Tabor et al, 2020), probably are correct. Such an interpretation is bolstered by the perspective that high-latitude regions in the Southern Hemisphere, such as Patagonia, Argentina, were once regarded as refugia for plants during the K/Pg mass-extinction event (Barreda et al, 2012), although this changed when Stiles et al (2020) discovered evidence of a megafloral mass-extinction event of approximately the same magnitude (~90% of species) and nature (destruction of broadleaved evergreen forests, resulting in leaf physiognomicbased drops in mean annual temperatures of −5°C) as that described from western North America by Johnson (1996Johnson ( , 2002, Wilf et al (2003) and Wilf and Johnson (2004). Although these discoveries are new, they were nonetheless predicted by Iglesias et al (2011) following the description of an early Paleocene megafloral assemblage (Iglesias et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This presumably explains many of the more enigmatic aspects of the patterns of plant succession across the K/Pg boundary, such as why Agathis characteristically replaced other araucarian conifers with a stronger resemblance to Araucaria Sections Bunya, Intermedia and Araucaria or Wollemia in both New Zealand and South America (Pole and Vajda, 2009;Escapa et al, 2018), although podocarps, which apparently have a high incidence of recalcitrant seeds (Wyse and Dickie, 2017), eventually rose to dominance (Pole and Vajda, 2009). Similarly, lauraceous species along with non-magnoliid "dicot" angiosperms suffered considerable extinction in Patagonia, although they quickly returned to dominance (Stiles et al, 2020), a pattern also observed about ten thousand kilometers to the north in the Raton Basin of the southern Western Interior of North America (Berry, 2019a). Because there was obviously little or no biogeographic continuity between these regions, these similar biogeographic patterns must be due to fundamental rules of tropical plant community assembly (i.e., ecological succession following an environmental catastrophe).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations